Revision of Aciuroides Hendel and Neoacanthoneura Hendel (Diptera: Ulidiidae: Pterocallini) - Kameneva, Elena P. (Zootaxa, 2012)
The genera Aciuroides and Neoacanthoneura occur only in Central and South America and are represented by 2 and 12 species, respectively. Eleven new species, Neoacanthoneura apicalis sp. n., N. brachioptera sp. n., N. chiroptera sp. n., N. dryas sp. n., N. geomyzina sp. n., N. goniata sp. n., N. euphrantina sp. n., N. steyskali sp. n., N. subapicalis sp. n., N. trypetina sp. n., N. trupaneina sp. n. are described, and the previously known species are redescribed and illustrated based on type material. The following synonymies and combinations are established: Aciuroides Hendel 1914 = Idanophana Hering 1938, new synonym; Aciuroides gephyra (Hering 1938), new combination (= Idanophana gephyra Hering 1938) = Aciuroides fasciata Hering 1941, new synonym = Idanophana missionarius Steyskal 1971, new synonym; Aciuroides insecta Hering 1941 = Aciuroides plaumanni Hering 1941, new synonym.